Education and Training of Specialist Sexual Offence Investigators in Victoria, Australia from 2009 to 2011 - Turnley, Jennifer Anne (2014)
The topic of training specifically designed for investigators of sexual offences has received little attention from academic researchers to date. Previous studies have not described training provided to police investigators of sexual offences in Australia. This thesis developed Turnley’s Framework for the Examination of Police Training in Sexual Assault Investigation, to examine and describe a Sexual Offences and Child Abuse Investigative Teams (SOCIT) Course, provided to Victorian Police from 2009 to 2011. This entailed triangulation of findings from non-participant observations of one SOCIT Course, with quantitative and qualitative data sourced though an in-depth interview with course trainers; feedback sheets voluntarily completed by trainees who undertook the course and responses from an online survey of 44 police who completed a course between 2009 and 2011. A description of the course design, resourcing, content, delivery, individual and organisational outcomes are presented as findings. Trainees reported the SOCIT course to be highly relevant for the work of specialist sexual assault investigators, with 80% of survey respondents self-reporting a change in their attitudes towards victims of sexual offences as a result of the SOCIT training. Despite these self-reports, findings from the survey indicate the maintenance of negative attitudes by some police in relation victims. The findings of this thesis concur and support findings of the Policing Just Outcomes Project with regard to the need for police to focus on, and refine the process of selection and recruitment, for this specialised area of police work